Investigation on microstructure and mechanical properties of inconel 725 printed by direct energy deposition - Lim, Aloysius Huan Da (Nanyang Technological University, 2024)
Inconel 725 commonly used in aerospace and marine industries for its excellent strength and corrosion resistance, these properties however are dictated by its microstructure. With additive manufacturing becoming an increasingly important manufacturing technique to allow damaged parts to be repaired to promote sustainability, printed Inconel 725 is being studied to compare its performance against traditional manufacturing techniques. This paper intends to gain insights of the microstructural features by using optical microscope, scanning electron microscope. Techniques like electron backscatter diffraction and energy dispersive spectroscopy will be used to characterize the Inconel 725 samples. The mechanical properties of Inconel 725 will be analysed with Vickers hardness test to compare how it can be affected by building height. This paper will then conclude by summarizing the notable results obtained and recommendations.